Kajian Optimalisasi Aset Milik PT. Perkebunan Nusantara XII (Persero) - Dwi Aryani Suryaningrum; Dyah Puspasari (Jurnal Ilmu Manajemen Advantage, 2019)
The economic growth of Surabaya also encourages the development of commercial businesses, one of which is the property business. But seeing the increasingly limited land in Surabaya, then the alternative is to optimize existing assets. The optimization is in the form of land use by establishing a property that can provide benefits so that the market value of a land becomes high. Mess Building PT. Perkebunan Nusantara XII (Persero) which is located on Jalan Embong Tanjung No.17 Surabaya has an area of ​​1,388 m2 and is in an area that has the potential to be developed into an alternative commercial property such as apartments, hotels, offices, and shops. The determination of the value of the Mess Building depends on land use, for this reason it is necessary to conduct a Highest and Best Use (HBU) analysis, which is physically possible, legally permitted, financially feasible, and has maximum productivity. The results obtained in this study were seen from the aspects of land, location, legal and financial alternatives of the hotel as the best land use that has the highest land value of IDR 52,253,874 / m2.